Effectiveness of a Family-Based Self-Management Intervention for Type 2 Diabetes Patients Receiving Family Doctor Contract Services: A Community-Based Randomized Controlled Trial - Lan Zhu; Jing Wang; Zhigang Pan; Wei Zhang; Jing Tang; Hua Yan; Fulai Shen; Yi Shen (Journal of Primary Care & Community Health)
Introduction: The community-based management of type 2 diabetes in China remains suboptimal. Incorporating family support presents a promising approach to enhancing facilitators and addressing barriers to effective diabetes self-management, particularly in the Chinese context where familial relationships and collective family responsibility play a central role in health-related decision-making and daily life. We aimed to validate a family support-based self-management behavioral intervention program, Systematic evaluation, core education, self-directed planning, triple feedback, and develop a habit program (SeCe-STRIVE). The program comprises 5 modules: systematic evaluation, core education, self-directed planning, triple feedback, and habit development. Research Design and Methods: We conducted a community-based, single-center, parallel randomized controlled trial in the Xietu community of Xuhui District, Shanghai. Eligible patients were randomly assigned to either the intervention or control group. Participants in the intervention group received the SeCe-STRIVE health management program based on family support, while those in the control group received the community-based follow-up management program for type 2 diabetes. The primary outcome measured was the total self-management behavior score and its changes across various dimensions from baseline. Secondary outcomes included family support, family function, diabetes knowledge, quality of life, self-efficacy, and biochemical markers. Post-intervention changes in both primary and secondary outcomes relative to baseline were analyzed using analysis of covariance. Results: The study ultimately included 113 participants in the intervention group and 112 in the control group. The intervention group’s total self-management behavior score improved by 12.74 (95% CI = 10.07, 15.40, P  < .001) points more than the control group. Across all dimensions of self-management behaviors, the intervention group showed greater improvement, including diet, exercise, blood glucose monitoring, foot care, and medication adherence. Participants with low family support exhibited greater improvements in self-management behaviors compared to those with high family support. The intervention group demonstrated significant improvements in family support, family function, diabetes knowledge, and self-efficacy. Although quality of life and biochemical indicators of glycated hemoglobin, fasting blood glucose, and blood lipids showed a decreasing trend, the differences were not statistically significant. Conclusions: Compared to the control group, patients with type 2 diabetes who received the SeCe-STRIVE program intervention showed significant improvements in self-management behaviors, accompanied by enhancements in family support, family functioning, and self-efficacy. Further large-scale, multi-center trials with longer follow-up periods are needed to confirm these results. Trial Registration: ChiCTR, ChiCTR2200060416. Registered 01 June 2022, https://www.chictr.org.cn/showproj.html?proj=167086